Corrosion Inhibition of Mild Steel in Hydrochloric Acid Environment Using Terephthaldehyde Based on Schiff Base: Gravimetric, Thermodynamic, and Computational Studies - Bahaa Sami Mahdi; Muna Khethier Abbass; Mustafa Khudhair Mohsin; Waleed Khalid Al-azzawi; Mahdi M. Hanoon; Mohammed Hliyil Hafiz Al-kaabi; Lina M. Shaker; Ahmed A. Al-amiery; Wan Nor Roslam Wan Isahak; Abdul Amir H. Kadhum; Mohd S. Takriff (Molecules, 2022)
Using traditional weight-loss tests, as well as different electrochemical techniques (potentiodynamic polarization and electrochemical impedance spectroscopy), we investigated the corrosion-inhibition performance of 2,2′-(1,4-phenylenebis(methanylylidene)) bis(N-(3-methoxyphenyl) hydrazinecarbothioamide) (PMBMH) as an inhibitor for mild steel in a 1 M hydrochloric acid solution. The maximum protection efficacy of 0.0005 M of PMBMH was 95%. Due to the creation of a protective adsorption layer instead of the adsorbed H2O molecules and acidic chloride ions, the existence of the investigated inhibitor reduced the corrosion rate and increased the inhibitory efficacy. The inhibition efficiency increased as the inhibitor concentration increased, but it decreased as the temperature increased. The PMBMH adsorption mode followed the Langmuir adsorption isotherm, with high adsorption-inhibition activity. Furthermore, the value of the <semantics>∆<msubsup>Gadso</msubsup> </semantics> indicated that PMBMH contributed to the physical and chemical adsorption onto the mild-steel surface. Moreover, density functional theory (DFT) helped in the calculation of the quantum chemical parameters for finding the correlation between the inhibition activity and the molecular structure. The experimental and theoretical findings in this investigation are in good agreement.